Environmental risk factors for cleft lip and palate in low-resource settings: a case-control study. (March 2019) - Auslander, Allyn; Mckean-Cowdin, Roberta; Brindopke, Frederick; Magee, Kathy; DiBona, Melissa; Magee, William
Abstract: Background: Cleft lip with or without palate is the most common birth defect with a global prevalence of 1 in 700 births. Although there is a clear algorithm of care in developed countries, the lack of access to surgery in low-income and middle-income countries (LMICs) means that millions of people live with this easily treated condition. Although smoke exposure from unsafe cooking practices no longer occurs in the developed world and is not routinely studied, exposure to smoke from cooking remains an important challenge to health in LMICs. We aimed to understand whether exposure to cooking smoke is associated with cleft lip and palate in these low-resource settings. Methods: We conducted a case–control study of mothers of a child with cleft lip with or without palate (cases) and population-matched mothers of children who do not have the condition (controls) in partnership with Operation Smile. Participants were from Vietnam, the Philippines, Honduras, Nicaragua, Morocco, Democratic Republic of the Congo, and Madagascar. Participants provided written consent and the University of Southern California gave ethical approval for the study. The primary exposure of interest was smoke inhalation in the form of smoking before or during pregnancy, paternal (ie, the father of the child) smoking, living with any smoker, or cooking indoors over a fire. We used logistic regression with multiple adjustment models to assess these smoke exposures as possible risk factors for cleft lip and palate. Findings: We included data from 2168 cases and 2080 controls, recruited between 2011 and 2017. We found that <1% of the mothers in our study smoked cigarettes, but 59·3% (n=1234) cases and 39·1% (n=848) controls cooked over a fire inside their home. We did not find a significant effect of household smoking, smoking 3 months before or during pregnancy, or paternal smoking in our data. Case mothers were 1·47 (95% CI 1·2–1·8) times more likely to cook over a fire indoors than were controls, after mutual adjustment for all other smoke exposure, confounders, and urban versus rural place of dwelling. Interpretation: Exposure to smoke while cooking is a well-established health risk in LMICs for a wide variety of diseases, but has never been studied with respect to cleft lip and palate. We have shown that it may play a role in the risk of cleft lip and palate, and that it may be a larger risk factor than active or passive tobacco smoke exposure. Exposures specific to low-resource settings must be taken into account when we study preventable risk factors in order to develop strategies that will address the populations at the highest risk of having to live with this condition. Funding: None.